Modelling the Work Flow of a Nuclear Waste Management Program - Mortensen, Kjeld Høyer; Pinci, Valerio (DAIMI Report Series, 1997)
In this paper we describe a modelling project to improve a nuclear waste management program in charge of the creation of a new system for the permanent disposal of nuclear waste. SADT (Structured Analysis and Design Technique) is used in order to provide a work-flow description of the functions to be performed by the waste management program. This description is then translated into a number of Coloured Petri Nets (CPN or CP-nets) corresponding to different program functions where additional behavioural inscriptions provide basis for simulation. Each of these CP-nets is simulated to produce timed event charts that are useful for understanding the behaviour of the program functions under different scenarios. Then all the CPN models are linked together to form a single stand-alone application that is useful for validating the interaction and cooperation between the different program functions. A technique for linking executable CPN models is developed for supporting large modelling projects and parallel development of independent CPN models.